In-Hospital Stroke Recurrence and Stroke After Transient Ischemic Attack. Issue 4 (April 2015) - Erdur, Hebun; Scheitz, Jan F.; Ebinger, Martin; Rocco, Andrea; Grittner, Ulrike; Meisel, Andreas; Rothwell, Peter M.; Endres, Matthias; Nolte, Christian H.
<x xml:space="preserve">Abstract</x> Background and Purpose— We aimed to assess the risk of recurrent ischemic events during hospitalization for stroke or transient ischemic attack (TIA) with optimal current management and to identify associated risk factors. Methods— We performed a retrospective analysis of all patients treated for acute ischemic stroke or TIA in 3 stroke units between 2010 and 2013. Recurrent stroke was defined as new persisting (≥24 hours) neurological deficit occurring >24 hours after the index event and not attributable to other causes of neurological deterioration. Cox proportional hazard regression identified risk factors associated with recurrent stroke. Results— The study included 5106 patients. During a median length of stay of 5 days (interquartile range, 4–8), stroke recurrence (or stroke after TIA) occurred in 40 patients (0.8%) and was independently associated with history of TIA, symptomatic carotid stenosis (≥70%), or other determined etiology. Patients with recurrent stroke and other determined etiology had cervical arterial dissection (n=2), primary angiitis of the central nervous system (n=1), giant cell arteritis (n=1), and lung cancer with nonbacterial thrombotic endocarditis (n=1). In patients with initial TIA or minor stroke (National Institutes of Health Stroke Scale ⩽5) recurrence was associated additionally with pneumonia after the inciting ischemic event but before stroke recurrence. Patients with initial stroke and aphasia had a lower stroke recurrence rate and there were no recurrences in patients with lacunar stroke. Recurrence was associated with significantly higher in-hospital mortality (17.5% versus 3.1%; P<0.001). Conclusions— In-hospital stroke recurrence was low with optimal current management. Patients with a history of TIA, severe symptomatic carotid stenosis, or uncommon causes of stroke were at higher risk. Pneumonia was associated with a higher risk of stroke recurrence in patients with initial TIA or minor stroke but not in the overall population studied. Aphasia may bias the detection rate by concealing new neurological symptoms.